An improved genetic linkage map for cowpea (Vigna unguiculata L.) combining AFLP, RFLP, RAPD, biochemical markers, and biological resistance traits - Ouédraogo, J.T.; Gowda, B.S.; Jean, M.; Close, T.J.; Ehlers, J.D.; Hall, A.E.; Gillaspie, A.G.; Roberts, P.A.; Ismail, Abdelbagi M.; Bruening, G.; Gepts, P.; Timko, M.P.; et al. (Canadian Science Publishing, 2002)
An improved genetic linkage map has been constructed for cowpea (Vigna unguiculata L. Walp.) based on the segregation of various molecular markers and biological resistance traits in a population of 94 recombinant inbred lines (RILs) derived from the cross between 'IT84S-2049' and '524B'. A set of 242 molecular markers, mostly amplified fragment length polymorphism (AFLP), linked to 17 biological resistance traits, resistance genes, and resistance gene analogs (RGAs) were scored for segregation within the parental and recombinant inbred lines. These data were used in conjunction with the 181 random amplified polymorphic DNA (RAPD), restriction fragment length polymorphism (RFLP), AFLP, and biochemical markers previously mapped to construct an integrated linkage map for cowpea. The new genetic map of cowpea consists of 11 linkage groups (LGs) spanning a total of 2670 cM, with an average distance of 6.43 cM between markers. Astonishingly, a large, contiguous portion of LG1 that had been undetected in previous mapping work was discovered. This region, spanning about 580 cM, is composed entirely of AFLP markers (54 in total). In addition to the construction of a new map, molecular markers associated with various biological resistance and (or) tolerance traits, resistance genes, and RGAs were also placed on the map, including markers for resistance to Striga gesnerioides races 1 and 3, CPMV, CPSMV, B1CMV, SBMV, Fusarium wilt, and root-knot nematodes. These markers will be useful for the development of tools for marker-assisted selection in cowpea breeding, as well as for subsequent map-based cloning of the various resistance genes.Key words: Cowpea, AFLP, RAPD, resistance gene analogs, genetic linkage map.